Implementation of “Do Not Resusitate (DNR)” In Indonesia's Law and the Study of Ethical Principles of Their Implementation - Kadek Radhitya Vidianditha; I Nyoman Bagiastra; Ria Tri Harini Dwi Rusiawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze and examine in depth the implementation of the " Do Not Resuscitate (DNR)" medical action in the perspective of legislation in Indonesia. This study also discusses and examines the ethical principles in the implementation of " Do Not Resuscitate (DNR)" as part of Euthanasia and pseudo-euthanasia. This research uses normative legal research methods, using a statutory approach (status approach), and a conceptual approach (conceptual approach). The results of this study are the first with not explicitly regulated the implementation of " Do Not Resuscitate (DNR)" as part of Euthanasia or pseudo euthanasia depending on the case and condition of the patient being treated by medical personnel in Indonesian legislation, making frequent conflicts both from the side of the patient or medical personnel. Second, several countries in the world already have national guidelines to make it easier to do " Do Not Resuscitate (DNR)", Indonesia, which only relies on ethical studies, is deemed insufficient for medical personnel to do " Do Not Resuscitate (DNR)", So there are often ethical dilemmas.